(untitled) - Bannister, Barbara A (London, 1996)
The introductory chapters set out the important definitions required for the understanding of infectious diseases and describes the nature and presentation of infection, its pathogenesis and scientific investigation. The diagnosis, management and control of individual infectious diseases are described in the systematic chapters. Each chapter introduces the range of diseases affecting the relavant system and a list of pathogens is presented for each disease in the approximate order of importance. For each individual disease there is a discussion of the microbiology and epidemiology of the relevant pathogens, the diagnosis and management of the disease and strategies for their prevention and control
Keywords: communicable diseases